2019
DOI: 10.1115/1.4043529
|View full text |Cite
|
Sign up to set email alerts
|

Individualizing Locator Adjustments of Assembly Fixtures Using a Digital Twin

Abstract: Implementing the concept of a digital twin in full production provides enough data on each individual assembly for real-time control of production processes. Taking advantage of this opening, this paper proposes individualized locator adjustments as a new method to improve the geometrical quality of assemblies. In this method, all locators in the assembly fixture can be adjusted for each individual assembly based on the scan data of the mating parts of that assembly. The optimal adjustment of every locator for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Furthermore, the joining process can be optimized with respect to geometrical quality. Locators can be adjusted [19], and spot welding sequences can be optimized [20] for each individual assembly. By those suggested adjustments, the geometrical quality of the assembly can be improved without changing the tolerances of the parts, which is beneficial from a cost perspective.…”
Section: Digital Twin Framework For Geometry Assurancementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the joining process can be optimized with respect to geometrical quality. Locators can be adjusted [19], and spot welding sequences can be optimized [20] for each individual assembly. By those suggested adjustments, the geometrical quality of the assembly can be improved without changing the tolerances of the parts, which is beneficial from a cost perspective.…”
Section: Digital Twin Framework For Geometry Assurancementioning
confidence: 99%
“…With this approach, studies on several industrial cases have shown that the variation of the final subassembly can be reduced up to 50%, compared to when no adjustments are done [18][19][20]. With the labeling digital model, digital shadow, and digital twin mentioned at the beginning of this section, a digital twin for geometry assurance can be interpreted as:…”
Section: Digital Twin Framework For Geometry Assurancementioning
confidence: 99%
See 1 more Smart Citation
“…With these simulation models, often referred to as digital twin, optimizations can be performed and more precise predictions can be made. Especially, for the automotive and aerospace industry, this principle is used for optimizing the assembly of thin parts, for example, sheet metal body parts as presented by A. Rezaei Aderiani et al [2]. Before simulations with digital twins were performed in the quality assurance processes, only physical measurements were compared.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal of DTs is to reduce the overall lifecycle cost of physical systems. In manufacturing systems, DTs enable us to better monitor, control, and optimize the processes [1][2][3][4]. The enabling technologies of manufacturing DTs include sensing [5], control [6], modeling and simulation [7], predictive maintenance [8], data analytics [9,10], lifecycle information management [11], and others.…”
Section: Introductionmentioning
confidence: 99%